The Future Of Management In The Era Of Artificial Intelligence - Sotvoldiev, Mirzoxidjon (International Conference on Global Trends and Innovations in Multidisciplinary Research, 2025)
This article analyzes the impact of artificial intelligence (AI) technologies on management systems, trends that are changing the processes of leadership and decision-making in the modern business environment. The article covers the role of artificial intelligence in management, its theoretical foundations, examples of international experience, and prospects for introducing these technologies in Uzbekistan. As an example of international experience, the role of artificial intelligence in the management systems of Google, Tesla, Amazon, Microsoft, and IBM is given. The prospects for introducing AI technologies in the business sector of Uzbekistan, existing obstacles, and development opportunities are also analyzed. The results show that artificial intelligence turns management into a more flexible, information-based, and innovative system. As a result of the introduction of artificial intelligence into management, the speed, accuracy and efficiency of decisions are increasing, and errors inherent in the human factor are decreasing. At the same time, the expansion of AI technologies is also creating new ethical, social and labor relations problems.The purpose of the study is to identify the scientific and theoretical foundations of the use of artificial intelligence in the management system, analyze international experience and develop proposals for the development of AI-based management in the conditions of Uzbekistan. The article studies theoretical and practical data based on comparative, systematic and analytical approaches.The results show that in the era of artificial intelligence, management is moving from intuitive decisions based on human thinking to a scientific management model based on data. This process is changing the philosophy of management, transforming management into an automated, analytical and adaptive system.